In need of publishing a paper to find a job or grant? Co-authorship without contributing: The rise of an ethical problem - Committee, Editorial (Austral Journal of Veterinary Sciences, 2019)
In need of publishing a paper to find a job or grant? Co-authorship without contributing: The rise of an ethical problem